2009
DOI: 10.1007/s10562-008-9829-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CuO-ZnO Catalyst Prepared by Decomposition of Carbonates Using Dielectric-Barrier Discharge Plasma

Abstract: In this work, we confirmed that dielectric barrier discharge (DBD) plasma is excellent for the decomposition of carbonates to prepare CuO-ZnO catalysts in a rapid and energy efficient way. According to the characterization using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and Field Emission Scanning Electron Microscope (FE-SEM), the DBD plasma generated CuO-ZnO catalyst was smaller in particle size with higher copper-zinc surface ratio, compared to the catalyst prepared thermally. Diffuse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…These results indicate that treatment with DBD can be used to replace thermal calcination for the decomposition of cobalt precursor molecules to oxides. There are two obvious advantages: first, DBD treatment can greatly reduce the decomposition time, and second, cobalt precursor decomposition can be achieved at low temperatures (less than 103°C) [18], which may avoid Co 3 O 4 aggregation that has been observed at high temperatures during thermal calcination. The data are presented in Table 1 and suggest that the complete decomposition rate of the prepared catalysts for 20% Co/SiO 2 is 31 ± 1%, which is further supported by the TGA results that are shown in Fig.…”
Section: The Effect Of Cobalt Precursor Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that treatment with DBD can be used to replace thermal calcination for the decomposition of cobalt precursor molecules to oxides. There are two obvious advantages: first, DBD treatment can greatly reduce the decomposition time, and second, cobalt precursor decomposition can be achieved at low temperatures (less than 103°C) [18], which may avoid Co 3 O 4 aggregation that has been observed at high temperatures during thermal calcination. The data are presented in Table 1 and suggest that the complete decomposition rate of the prepared catalysts for 20% Co/SiO 2 is 31 ± 1%, which is further supported by the TGA results that are shown in Fig.…”
Section: The Effect Of Cobalt Precursor Decompositionmentioning
confidence: 99%
“…Some researchers have investigated the use of DBD plasma for preparing catalysts. Kuai et al [18] reported that DBD plasma is excellent for the decomposition of carbonates to prepare CuO-ZnO catalysts in a rapid and energy efficient manner. Li et al [19,20] investigated Ni dispersion, stability, and the catalytic performance of alumina-supported catalysts that were pretreated with DBD argon plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Most often, catalyst are synthesized using (wet/dry) impregnation or (co‐)precipitation which combines several unit operations. It can be useful to add plasma treatment to the standard process to enhance several catalyst properties such as the dispersion and the particle sizes,11, 69–73 but a more interesting approach exists in the replacement of the reduction or calcination step by a plasma treatment 74–80…”
Section: Catalyst Treatmentmentioning
confidence: 99%
“…Several authors investigated the use of a non‐equilibrium plasma treatment to replace a high temperature treatment of catalysts because such treatments tend to lead to increased particle sizes and decreased dispersions of the active species 74–78. The low temperature (less than a few 100°) of the non‐equilibrium plasmas could prevent the negative side effects of a thermal calcination treatment.…”
Section: Catalyst Treatmentmentioning
confidence: 99%
“…We aim to develop a general plasma method for the template removal from various zeolites and also mesoporous materials. DBD is one of the non-thermal plasma phenomena, which is characterized by high electron temperatures (10,000-100,000 K) and low gas temperatures (as low as room temperature) [14,15]. A major advantage of the DBD plasma is that it can be operated at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%